PENANGANAN HAMBATAN EPISTEMOLOGI PEMAHAMAN KONSEPTUAL MATEMATIS SISWA MELALUI PENDEKATAN RECIPROCAL TEACHING DENGAN TUTOR SEBAYA - Harun, Harun; Sugiatno, Sugiatno; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to explain and describe the conceptual understanding of mathematical epistemology barriers students before and after are handled through Reciprocal Teaching with a peer tutor at the students of SMP Islam Bawari. The methods used in this research is the pre-eksperiement: one-preteset-group posttest design. Data collection techniques used in this research is the tests and interviews. Data collection tools used in the form of diagnostic tests, which contains 4 question essay and interview guidelines. The data in this study a greater emphasis on qualitative aspects and focuses on conceptual understanding students ' mathematical in resolving the problem. The results obtained are obstacles before students are given epistemology handling is quite high because the percentage of the average test score of only 38% diagnostiknya. After being given the handling through Reciprocal Teaching with a peer tutor, barriers addressed students this epistemology can be seen on the average percentage of diagnostic test scores of students increased to 88%. Keywords: Epistemological barriers, Mathematical conceptual understanding, Through reciprocal teaching with a peer tutor.